PENGARUH PEMBERIAN CAMPURAN SARI KUNYIT DAN MADU MELALUI AIR MINUM TERHADAP KUALITAS FISIK DAGING BROILER - Trisna I. G. A. G. W.; I. P. A. Astawa; S. A. Lindawati (Fakultas Peternakan Universitas Udayana, 2025)
This study aims to determine the effect of administering a mixture of turmeric extract and honey through drinking water on the physical quality of broiler meat.The broilers were divided into four treatment groups: P0 (control, no turmeric extract and honey), P1 (1% mixture of turmeric extract and honey), P2 (2% mixture of turmeric extract and honey), and P3 (3% mixture of turmeric extract and honey) through drinking water. Observed parameters included meat pH, water-holding capacity (WHC), cooking loss, drip loss, and meat color. Increasing the level of turmeric extract and honey tended to enhance the meat color due to the absorption of curcumin into the tissues. The pH values remained within the normal range (5.6–5,9), indicating that the meat was in good condition and fit for consumption. Water holding capacity (27–32%), cooking loss (33–34%), and drip loss (12–14%) were all within the normal range, with a tendency for increased water holding capacity in treatments supplemented with turmeric and honey. In terms of meat color, a decrease in lightness (L*) and redness (a*) was observed in the turmeric and honey extract treatments compared to the control, although the differences were not statistically significant. However, the yellowness value (b*) in treatment P3 showed a significant decrease, possibly due to the degradation of curcumin pigments at high concentrations. ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh pemberian campuran sari kunyit dan madu melalui air minum terhadap kualitas fisik daging broiler. Broiler diberikan perlakuan dengan empat kelompok, yaitu P0 (tanpa penambahan sari kunyit dan madu), P1 = 1% (campuran sari kunyit dan madu), P2 = 2% (campuran sari kunyit dan madu) P3 = 3% (campuran sari kunyit dan madu) melalui air minum. Parameter yang diamati meliputi pH daging, daya ikat air (DIA), susut masak, susut mentah dan warna daging. Peningkatan level pemberian sari kunyit dan madu cenderung meningkatkan warna daging akibat zat kurkumin yang meresap ke dalam jaringan. Nilai pH daging masih berada dalam kisaran normal (5,6–5,9), yang menunjukkan bahwa daging dalam kondisi baik dan layak konsumsi. Daya ikat air (27-32%), susut masak (33-34%), dan susut mentah (12-14%) masing- masing juga berada dalam rentang normal, dengan kecenderungan peningkatan daya ikat air pada perlakuan dengan kunyit dan madu. Dari aspek warna, terjadi penurunan kecerahan (L*) dan kemerahan (a*) pada perlakuan sari kunyit dan madu dibanding kontrol, meskipun tidak signifikan. Namun, nilai kekuningan (b*) pada P3 mengalami penurunan signifikan, yang kemungkinan disebabkan oleh degradasi pigmen kurkumin dalam dosis tinggi.